1992
DOI: 10.1007/bf00685553
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 9-dimethylaminomethyl-10-hydroxycamptothecin against xenografts derived from adult and childhood solid tumors

Abstract: The topoisomerase I inhibitor 9-dimethylaminomethyl-10-hydroxycamptothecin (topotecan) was evaluated against a panel of xenografts comprising four lines of adult colon adenocarcinoma, three colon tumors derived from adolescents, six childhood rhabdomyosarcomas from previously untreated patients as well as sublines selected in vivo for resistance to vincristine and melphalan, and three lines of childhood osteogenic sarcoma. Efficacy was determined at maximal tolerated dose levels using intermittent i.p. adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
103
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(106 citation statements)
references
References 19 publications
3
103
0
Order By: Relevance
“…Antitumour activity has been demonstrated in preclinical models and in phase I and II studies Rowinsky et al, 1992;Wall et al, 1992;Blaney et al, 1993;Hochster et al, 1994;Verweij et al, 1993;Creemers et al, 1994 for review). The results of preclinical and clinical studies indicate enhanced antineoplastic activity of topotecan when administered daily for prolonged periods of time (Giovanella et al, 1989;Burris et al, 1992;Houghton et al, 1992;Rowinsky et al, 1992;Hochster et al, 1994;Verweij et al, 1993). Also, preclinical studies with oral topotecan have shown that it has efficacy against rhabdomyosarcoma and colon carcinoma in mice (Houghton et al, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antitumour activity has been demonstrated in preclinical models and in phase I and II studies Rowinsky et al, 1992;Wall et al, 1992;Blaney et al, 1993;Hochster et al, 1994;Verweij et al, 1993;Creemers et al, 1994 for review). The results of preclinical and clinical studies indicate enhanced antineoplastic activity of topotecan when administered daily for prolonged periods of time (Giovanella et al, 1989;Burris et al, 1992;Houghton et al, 1992;Rowinsky et al, 1992;Hochster et al, 1994;Verweij et al, 1993). Also, preclinical studies with oral topotecan have shown that it has efficacy against rhabdomyosarcoma and colon carcinoma in mice (Houghton et al, 1992).…”
mentioning
confidence: 99%
“…The results of preclinical and clinical studies indicate enhanced antineoplastic activity of topotecan when administered daily for prolonged periods of time (Giovanella et al, 1989;Burris et al, 1992;Houghton et al, 1992;Rowinsky et al, 1992;Hochster et al, 1994;Verweij et al, 1993). Also, preclinical studies with oral topotecan have shown that it has efficacy against rhabdomyosarcoma and colon carcinoma in mice (Houghton et al, 1992). The unique mechanism of action and lack of cross-resistance evidence with many wellknown currently available anti-tumour agents may provide therapeutic advantage in first-line or second-line chemotherapy.…”
mentioning
confidence: 99%
“…A single optimal schedule could not be determined from the early preclinical in vivo studies (Dancey and Eisenhauer, 1996), although support for protracted schedules was obtained from some tumour model systems (Houghton et al, 1992). Nevertheless, the most commonly used clinical phase II schedule, a daily x five schedule, has been compared with more protracted schedules without any apparent advantage of the latter (Dancey and Eisenhauer, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Maximizing drug exposure to cells (particularly those with long cell-cycle times and low growth fractions) in S-phase can be achieved using protracted administration schedules such as daily for five days for two to three weeks (68). Studies of topotecan in xenograft models demonstrated the superiority of protracted schedules of administration over high doses administered Intermittently (68).…”
Section: Topotecanmentioning
confidence: 99%
“…Maximizing drug exposure to cells (particularly those with long cell-cycle times and low growth fractions) in S-phase can be achieved using protracted administration schedules such as daily for five days for two to three weeks (68). Studies of topotecan in xenograft models demonstrated the superiority of protracted schedules of administration over high doses administered Intermittently (68). Based on the strength of these preclinical data, Santana and colleagues evaluated the protracted administration with pharmacokinetically guided dosing of topotecan to minimize variability in systemic exposure and achieve the putatively effective topotecan systemic exposure in children.…”
Section: Topotecanmentioning
confidence: 99%